Zirconia-Yttria-Alumino silicate glass-based erbium-doped fibres as a medium for q-switched and mode-locked pulse generation / Kavintheran a/l Thambiratnam - Thambiratnam, Kavintheran (2014)
In this research, the fabrication and characterization of zirconia–yttria–alumino silicate glassbased erbium-doped fibres as well as their application as the gain media for compact fast and ultra-fast pulsed sources is presented. The fabrication process is similar to that of a conventional erbium doped fibre, with the ZrO2 co-dopants incorporated into the silica host during solution doping. Morphological studies of the drawn fibres reveal a core with a diameter of approximately 10 μm. Tunneling electron microscope scanning shows the presence of ZrO2 rich micro-crystallites, while X-ray diffraction analysis indicates the formation of tetragonal ZrO2 structures. Spectral characterization of the fibres show attenuation peaks at 980 nm and 1550 nm, with sample designated ZEr-B having absorption rates of 22.0 dB/m and 53.0 dB/m at 980 and 1550 nm respectively as well as a fluorescence life-time of 10.86 ms, as well as a W-profile refractive index. A 3 m long ZEr-B fiber with a dopant concentration of about 3880 ppm/wt is used to generate an amplified spontaneous emission spectrum. The fibres amplified spontaneous emission spectrum output differs substantially from that of a conventional erbium doped fibre of the same length, rising to a peak region at 1530 nm, followed by a short ‘plateau’ before decreasing. As a fibre amplifier a gain of around 28.0 dB near 1530 nm and a relatively flat gain of between 22.0 to 25.0 dB at the plateau region is obtained, together with a noise figure of approximately 14.1 dB for an input signal of -30 dBm. The fiber can also generate a single-longitudinal mode output, ranging from 1533.8 nm to 1545.0 nm at output powers of more than -8.9 dBm with an average signal-to-noise ratio of more than 50 dB. Additionally, the fiber allows non-linear interactions to occur at lower signal intensities than normal, with a four-wave-mixing output adhering to theoretically predicted models. The average four-wavemixing power level is -45 dBm at approximately 1565 nm, with a non-linear coefficient of 14 W-1km-1 with chromatic and dispersion slopes of 28.45 ps/nm.km and 3.63 ps/nm2.km. The erbium-doped zirconia fiber is also used in conjunction with gaphene and singlewalled carbon nanotubes based passive saturable absorbers to generate fast and ultrafast pulses is examined. Using a 3 m long ZEr-B with single-walled carbon nanotubes suspended in a polymer host generates Q-switched pulses with a repetition rate of 14.20 kHz and corresponding pulse width of 8.6 μs at a maximum pump power of 141.8 mW, as well as an average pulses output power of 270.0 μW and maximum pulse energy of 19.02 nJ. Using the graphene based saturable absorber gives a 50.1 kHz pulse train with a pulse width, energy and peak power of 4.6 μs, 16.8 nJ and 3.6 mW respectively. When mode-locked, the ZEr-B combined with the graphene based saturable absorber generates ultrafast pulses with an average output power, pulse energy and peak power of approximately 1.6 mW, 23.1 pJ and 31.6 W respectively as well as a pulse width of 730 fs and repetition rate of the pulses is 69.3 MHz. Using the single-walled carbon nanotubes composite as a saturable absorber gives mode-locked pulses with a repetition rate and peak power of 17.74 MHz and 14.09 W as well as average output power of 180 μW and pulse duration of approximately 720 fs at the fullwidth at half maximum point, with a pulse energy of 0.01 nJ. The generated pulses are stable and consistent, and allow them to be deployed with a high degree of confidence and reliability in multiple practical applications.